The first UK measurements of nitryl chloride using a chemical ionization mass spectrometer in central London in the summer of 2012, and an investigation of the role of Cl atom oxidation. Issue 11 (1st June 2015) - Bannan, Thomas J.; Booth, A. Murray; Bacak, Asan; Muller, Jennifer B. A.; Leather, Kimberley E.; Le Breton, Michael; Jones, Benjamin; Young, Dominique; Coe, Hugh; Allan, James; Visser, Suzanne; Slowik, Jay G.; et al.
Abstract: The first nitryl chloride (ClNO2 ) measurements in the UK were made during the summer 2012 ClearfLo campaign with a chemical ionization mass spectrometer, utilizing an I − ionization scheme. Concentrations of ClNO2 exceeded detectable limits (11 ppt) every night with a maximum concentration of 724 ppt. A diurnal profile of ClNO2 peaking between 4 and 5 A.M., decreasing directly after sunrise, was observed. Concentrations of ClNO2 above the detection limit are generally observed between 8 P.M. and 11 A.M. Different ratios of the production of ClNO2 :N2 O5 were observed throughout with both positive and negative correlations between the two species being reported. The photolysis of ClNO2 and a box model utilizing the Master Chemical Mechanism modified to include chlorine chemistry was used to calculate Cl atom concentrations. Simultaneous measurements of hydroxyl radicals (OH) using low pressure laser‐induced fluorescence and ozone enabled the relative importance of the oxidation of three groups of measured VOCs (alkanes, alkenes, and alkynes) by OH radicals, Cl atoms, and O3 to be compared. For the day with the maximum calculated Cl atom concentration, Cl atoms in the early morning were the dominant oxidant for alkanes and, over the entire day, contributed 15%, 3%, and 26% toward the oxidation of alkanes, alkenes, and alkynes, respectively. Key Points: The first UK measurements of ClNO2 using CIMS Relationships between N2 O5 and ClNO2 were dependent on air mass origins Cl oxidizes 14.5%, 2.6%, and 25% of alkanes, alkenes, and alkynes